THE ROLE OF GAME TECHNOLOGIES IN MILITARY-PATRIOTIC EDUCATION - Новичихин Н.В. (Bright Mind Publishing, 2025)
The article examines the role of game-based technologies in the process of military-patriotic education of youth. The author emphasizes that, in the context of global challenges and digitalization, game-based learning forms contribute to the effective development of patriotic feelings, leadership qualities, responsibility, and teamwork among the younger generation. The analysis of domestic and international pedagogical experience demonstrates that the use of role-playing, simulation, and digital games not only increases students’ motivation but also promotes the development of cognitive, communicative, and practical competencies. Special attention is given to the need for adapting game technologies to national and cultural traditions, which enhances their educational potential. The article concludes that game-based methods have become a key tool for shaping civic maturity and preparing young people for the defense of their homeland.